2006
DOI: 10.1158/1078-0432.ccr-06-1272
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Methylation Patterns of Cancer Genes in Salivary Gland Tumors

Abstract: Purpose: We investigated the methylation status and protein expression of four tumor suppressor genes to determine their role in salivary gland tumorigenesis. Experimental Design: We performed methylation-specific PCR and protein analyses of 29 normal salivary glands, 23 benign, and 79 malignant salivary gland neoplasms to determine the pattern and potential diagnostic and/or biological role of the RASSF1, RARb2, DAPK, and MGMT tumor suppressor gene methylation in these tumors. Results: No methylation was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 46 publications
1
47
1
Order By: Relevance
“…Recent studies evidenced that epigenetic alterations may play a role in the development and progression of SGT (32)(33)(34)(35). However, a relatively limited variety of SGT histotypes and genes analyzed for epigenetic regulation has been examined (36).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies evidenced that epigenetic alterations may play a role in the development and progression of SGT (32)(33)(34)(35). However, a relatively limited variety of SGT histotypes and genes analyzed for epigenetic regulation has been examined (36).…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylation of the tumor suppressor genes p16INK4a, p14ARF, p27Kip1, E-cadherin, 14-3-3 , RASSF1A, DAPK, MGMT, RAR ␤ 2 and RB1 has been demonstrated in some cases of salivary gland neoplasms [9][10][11][12][13][14]22] . Also, overexpression of various DNMTs in lung cancer may result in promoter hypermethylation of multiple tumor suppressor genes which then leads to poor prognosis [18] .…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic silencing of gene expression by promoter CpG island hypermethylation has been shown to be important in the formation of a variety of cancers including oral squamous cell carcinoma [8] . Indeed, several studies have demonstrated hypermethylation events in ACC [9][10][11] , MEC [11][12][13] , PA [11][12][13][14] , malignant PA [10] , salivary duct carcinoma [11] and acinic cell carcinoma [11] .…”
Section: Introductionmentioning
confidence: 99%
“…All of which are known for their ability to suppress vital cellular processes, including cell-cycle regulation, apoptosis, DNA repair, differentiation, and metastasis (34 -38). In a previous study, we used the MSP method to analyze the methylation status of some of these genes in these tumors (39). However, because of the arbitrary and qualitative nature of the MSP technique, the need for more objective and quantitative assessment of methylation has recently been raised (26).…”
mentioning
confidence: 99%